Thermally and electrochemically induced electrode/electrolyte interfaces in solid oxide fuel cells: An AFM and EIS Study - Jiang, San Ping (Electrochemical Society Inc., 2015)
In high temperature solid oxide fuel cells (SOFCs), electrode/electrolyte interfaces play a critical role in the electrocatalytic activity and durability of the cells. In this study, thermally and electrochemically induced electrode/electrolyte interfaces were investigated on pre-sintered and in situ assembled (La0.8Sr0.2)0.90MnO3 (LSM) and La0.6Sr0.4Co0.2Fe0.8O3-δ (LSCF) electrodes on Y2O3-ZrO2 (YSZ) and Gd0.2Ce0.8O2 (GDC) electrolytes, using atomic force microscopy (AFM) and electrochemical impedance spectroscopy (EIS). The results indicate that thermally induced interface is characterized by convex contact rings with depth of 100–400 nm and diameter in agreement with the particle size of pre-sintered LSM and LSCF electrodes, while the electrochemically induced interfaces under cathodic polarization conditions on in situ assembled electrodes are characterized by particle-shaped contact marks or clusters (50–100 nm in diameter). The number and distribution of contact clusters depend on the cathodic current density as well as the electrode and electrolyte materials. The contact clusters on the in situ assembled LSCF/GDC interface are substantially smaller than that on the in situ assembled LSM/GDC interface likely due to the high mixed ionic and electronic conductivities of LSCF materials. The results show that the electrochemically induced interface is most likely resulting from the incorporation of oxygen species and cation interdiffusion under cathodic polarization conditions. However, the electrocatalytic activity of electrochemically induced electrode/electrolyte interfaces is comparable to the thermally induced interfaces for the O2 reduction reaction under SOFC operation conditions.